Enhancement of mechanical properties of experimental composite by Fuller's earth nanofibers for cervical restoration1. Issue 6 (9th February 2013) - Houshyar, Aydin; Khavandi, Ali Reza; Javadpour, Jafar; Samani, Saeed; Naimi‐Jamal, Mohammad Reza; Atai, Mohammad
Abstract: In this research, we studied improvement of mechanical properties of dimethacrylate‐silica based dental composites by addition of Fuller's Earth (FE) clay. Three composites were made as base compounds consisting of 68, 58, and 48 wt % resin and 31, 41, and 51 wt % silica, respectively. Afterward, the composites were modified by adding FE. Mechanical properties including flexural strength, flexural modulus, work‐of‐fracture, fracture toughness, and microhardness were measured. Clay particles and fracture surface of composites consisting of 51 wt % silica (with and without FE) were examined by SEM. Measured results showed that flexural strength, work‐of‐fracture, flexural modulus, and microhardness of all composites increased by including FE nanofibers. Fracture toughness except for composite including 51 wt % silica had similar variations. It seems that locating FE nanofibers in weak resin region among silica particles leads to strengthening mechanisms, such as bridging and crack deflection, which cause improvement in mechanical properties. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 2013.